2022
DOI: 10.4070/kcj.2022.0258
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Patent Foramen Ovale Closure After Stroke

Abstract: Author's summary Recent several randomized clinical trials have shown that percutaneous patent foramen ovale (PFO) closure reduced the stroke recurrence compared to the medical therapy alone in patients with a PFO-associated stroke. Nevertheless, optimal patient selection for PFO closure has not been clarified. In the current paper, we discuss the characteristics of PFO-associated strokes and discuss the recently published evidence and patient selection for PFO closure in patients with ischemic stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…We read with great interest and appreciation the recently published article by Lee and Kim. 1) We also found many impressive concepts addressed in our recently published review. 2) In light of those topics, we wondered about some challenging issues and blind spots.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…We read with great interest and appreciation the recently published article by Lee and Kim. 1) We also found many impressive concepts addressed in our recently published review. 2) In light of those topics, we wondered about some challenging issues and blind spots.…”
mentioning
confidence: 64%
“…The authors 1) mention that recent randomized clinical trials have demonstrated the reduction of patent foramen ovale (PFO)-associated stroke recurrence by PFO closure compared to medical treatment. Including six randomized controlled trials, a recent meta-analysis 3) showed no significant difference in net clinical benefit between PFO closure and medical treatment, emphasizing individualized therapy.…”
mentioning
confidence: 99%
“…We sincerely appreciate the letter by Dell’Angela and Nicolosi 1) for our recently published article regarding a percutaneous patent foramen ovale (PFO) closure after a PFO-associated stroke. 2) They raised the concern about whether percutaneous PFO closure would be beneficial in terms of the safety of PFO closure.…”
mentioning
confidence: 99%